REALIZATION OF STATISTICAL INVENTORY OF THE VIRGIN BEECH FOREST IN UHOLSKO-SHYROKOLUZHANSKYY MASSIF - Havrylyuk, Serhiy; Khomyuk , Andriy (Forestry, Forest, Paper and Woodworking Industry, 2024)
This article provides a short overview on the statistical inventory of the virgin beech forest in the “Uholsko-Shyrokoluzhanskyy massif” which was held in July-August 2010 as a result of Swiss-Ukrainian cooperation.